Malaria Epidemiological Situation in Italy and Evaluation of Malaria Incidence in Italian Travelers - Romi, Roberto; Sabatinelli, Guido; Majori, Giancarlo (Journal of travel medicine, 2001)
Malaria was endemic throughout the country until it was eradicated nearly 50 years ago. Since then, mainly imported malaria cases have been reported to the National Health Service, with an increasing trend. The aim of this study was to present a detailed analysis of the current epidemiological situation of malaria in Italy, and to make a first attempt to calculate the incidence of malaria in Italian international travelers. An archive of confirmed malaria cases is available at the Istituto Superiore di Sanità (ISS), the National Institute of Health of Italy, based on the mandatory report system. Data from each case report reported to the ISS from 1989 to 1997 have been analyzed. An evaluation of malaria incidence in Italian travelers has been also performed for the same period, based on the statistics provided by the Ministry of Transport. From 1989 to 1997, a total of 5,898 microscopically confirmed malaria cases have been reported. Of these, 5,773 (97.9%) were imported cases, 106 cases (1.8%) were relapses of Plasmodium vivax or Plasmodium ovale infections, and 19 cases (0.3%) occurred in subjects who had never been out of Italy. During the period of study, 55 deaths due to Plasmodium falciparum malaria were reported, with a mean fatality rate of 1.2%. Malaria incidence in Italians who traveled to Africa was estimated to be 1.5/1000. These figures appeared to be 10-20 and 30-40 times greater than that recorded in travelers to Asia (0.11/1000) and Central-South America (0.04/1000) respectively. From 1989 to 1997, there has been a remarkable increase in the total number of imported malaria cases in Italy, which reached a peak of more than 800 cases/year in 1997. A constant increase in the number of cases affecting foreigners has been reported, while the cases among Italians have remained stable. From 1989 to 1997 the number of Italian intercontinental travelers has nearly doubled, but malaria incidence has remained quite stable.